SEMANTIC CATEGORIES OF REPORTING VERBS IN ONLINE NEWS ARTICLES - Iin Ruminda (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2016)
Reporting as a feature of a news genre has been an interesting research for many language researchers currently. As the use of the media in reporting other people’s ideas becomes more vary, the focus of the research is widely developed. One of the interesting reporting devices to analyze is the reporting verbs which have the main function of reporting other’s statements. This article will analyze the semantic categories of these verbs used in news articles published in 4 online news media. The theories from Biber, et al. (2002) equipped by Quirk (1985) are applied to analyze this problem. The findings show that there are three semantic categories found in the reporting verbs used in online news article. Those are classified into communication, activity, and mental verbs.